ADMINISTRATIVE AND ORGANIZATIONAL ASPECTS OF FUNCTIONING OF THE SYSTEM OF AVAILABILITY NARCOTIC AND PSYCHOTROPIC MEDICINAL PREPARATIONS FOR PATIENTS WHO NEED THEM - I. A. Kaminskaya; I. N. Tyurenkov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
Narcotic drugs and psychotropic substances still remain indispensable in medicine. One of the top priorities of health care is to ensure the required availability of this group of drugs. The development of an effective system which can ensure crucially important availability of narcotic and psychotropic agents to people who need them for medical purposes must rely on the identification and analysis of the nature and specificity of the problems related to them as well as the ways of solving these problems. ThePurpose of the Study was to explore the constituents of the system ensuring medicinal availability of narcotic and psychotropic agents and to identify the factors hindering the availability of this group of medicinal agents.Materials and Methods. The study involved the systematic review analysis of the scientific publications and guidance  documents regulating various aspects of activities involving the turnover of controlled drugs, and the results of surveys and interviews in which medical and pharmaceutical professionals were engaged. The study employed the methods of content analysis, logical and functional analysis, etc.Results and Discussion. The system of narcotic and psychotropic drug (NPD) availability for patients who need them is currently going through reforms which have been conditioned by low accessibilty of these drugs when used for medical purposes. Those engaged in the drug supply system including medical and pharmaceutical professionals point out that excessive bureaucratization of the system of NPD supply and availability, complexity of documentation and paperwork reporting thedrug flow, costliness of these activities, and strict liability account for low availability of such drugs. To ensure the rights of the citizens to relieve pain due to diseases or medical interventions, a number of changes in the laws and regulations have been made. They have simplified the requirements for NPD turnover in regard to administering, prescribing and dispensing the drugs. However, the findings of the studies which have been conducted demonstrate that the massive reforms of the regulatory framework aiming to change the situation are not actually implemented. The specialists involved in the field prefer not to enforce new laws and make every possible effort to avoid using new regulations instead and search for the opportunities either to minimize the activities involving controlled medicinal agentsor to refuse them altogether. In this situation, patients who need opioid analgesics, even within a favourable regulatory framework, are facing a lot of problems when the drugs are prescribed or dispersed.Сonclusions: In this case, a solution of the problem of low availability of NPD must involve the improvement of administrative management of the availability system at the level of medical and pharmaceutical organizations.